Negative electrode material, preparation method thereof, negative electrode sheet, and battery

CN120690827BActive Publication Date: 2026-10-27JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510732901.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-03
Publication Date
2026-10-27
Estimated Expiration
2045-06-03

AI Technical Summary

Technical Problem

然而,由于硬碳的表面缺陷多、比表面积大,导致首次不可逆容量损失大,循环衰减快,表面副反应多,与此同时,硬碳的电子导电性也较差,这些问题极大地限制了其在钠离子电池中的应用

Benefits of technology

[0042]在本申请实施例中,硬碳材料经第一包覆层(软碳)包覆后,可以有效降低硬碳材料的比表面积,提升硬碳材料的首次效率,同时也有益于实际应用的浆料加工。并且,硬碳材料包覆第一包覆层后,还具有第二包覆层,其中第二包覆层可以作为保护层,防止电解液与活性物质直接接触,减少副反应的发生,提升负极材料的循环稳定性;且第二包覆层中的分子筛本身具有有序的孔结构,能够允许钠离子快速达到活性层,在不影响钠离子的传输的同时,能加速钠离子的去溶剂化过程,进一步提升负极材料的动力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120690827B_ABST
    Figure CN120690827B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a negative electrode material, a preparation method thereof, a negative electrode sheet and a battery. The negative electrode material comprises: a hard carbon material, a first coating layer coated on at least part of the surface of the hard carbon material, and a second coating layer coated on at least part of the surface of the first coating layer; the first coating layer comprises soft carbon; and the second coating layer comprises a molecular sieve. After the hard carbon material is coated with the first coating layer (soft carbon), the specific surface area of the hard carbon material can be effectively reduced, the first efficiency of the hard carbon material is improved, and the slurry processing in actual application is also beneficial. Moreover, after the hard carbon material is coated with the first coating layer, the hard carbon material is further coated with the second coating layer, the second coating layer can serve as a protective layer, direct contact between electrolyte and active material is prevented, the occurrence of a side reaction is reduced, and the cycle stability of the negative electrode material is improved; and the molecular sieve in the second coating layer has an ordered pore structure and can allow sodium ions to quickly reach an active layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a negative electrode material, its preparation method, a negative electrode sheet, and a battery. Background Technology

[0002] Sodium-ion batteries (SIBs) have gained attention due to their low cost, abundant sodium resources, and similar working principles to lithium-ion batteries (LIBs), particularly in large-scale energy storage and slow-speed transportation, where they are expected to become a candidate energy storage technology to partially replace LIBs. Since sodium has a larger radius than lithium, finding a suitable sodium energy storage electrode is crucial. Hard carbon, with its large interlayer spacing, well-developed pore structure, and abundant defect sites, has been considered an ideal anode material for sodium-ion batteries. However, the numerous surface defects and large specific surface area of ​​hard carbon lead to significant initial irreversible capacity loss, rapid cycle decay, and numerous surface side reactions. Simultaneously, hard carbon also exhibits poor electronic conductivity, which greatly limits its application in sodium-ion batteries. Currently, to address this issue, related technologies employ a non-metallic coating to prevent electrolyte contact with the hard carbon surface. However, this method also hinders sodium ions from entering the active material, resulting in poor rate performance and sodium deposition.

[0003] Therefore, how to rationally construct hard carbon anode materials and improve their initial efficiency and cycle stability without affecting other properties has become a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a negative electrode material and its preparation method, a negative electrode sheet, and a battery, which can improve the initial efficiency and cycle stability of the battery without affecting other battery performance characteristics.

[0005] To solve the above-mentioned technical problems, this application is implemented as follows:

[0006] According to one aspect of this application, an embodiment of this application provides a negative electrode material, the negative electrode material comprising: a hard carbon material, a first coating layer covering at least a portion of the surface of the hard carbon material, and a second coating layer covering at least a portion of the surface of the first coating layer;

[0007] The first coating layer comprises soft carbon;

[0008] The second coating layer includes a molecular sieve.

[0009] In some of these embodiments, the thickness of the first coating layer is 100 nm to 200 nm.

[0010] In some of these embodiments, the soft carbon includes at least one of pitch-based soft carbon, tar-based soft carbon, or wood-based soft carbon.

[0011] In some of these embodiments, the thickness of the second coating layer is 10 nm to 50 nm.

[0012] In some embodiments, the second coating layer comprises a molecular sieve, the molecular sieve comprising at least one of AlPO4-5, SiO2, or Al2O3.

[0013] In some of these embodiments, the pore size of the molecular sieve is ≤2nm.

[0014] In some of these embodiments, the particle size of the hard carbon material is 4µm to 10µm.

[0015] In some of these embodiments, the hard carbon material has a porous structure.

[0016] In some of these embodiments, the hard carbon material has a pore size of 2 nm to 10 nm.

[0017] In some embodiments, the porosity of the hard carbon material is 0.2% to 0.6%.

[0018] According to another aspect of this application, embodiments of this application provide a method for preparing a negative electrode material, comprising the following steps:

[0019] Hard carbon material and soft carbon material are mixed in a first solvent, dried, and then calcined to obtain a hard carbon material with a soft carbon coating layer on the surface.

[0020] Hard carbon material with a soft carbon coating on its surface and molecular sieve raw material are mixed in a second solvent and subjected to a hydrothermal reaction. After heat treatment, the negative electrode material is obtained.

[0021] The negative electrode material includes: hard carbon material, a first coating layer covering at least a portion of the surface of the hard carbon material, and a second coating layer covering at least a portion of the surface of the first coating layer; the first coating layer includes soft carbon; and the second coating layer includes a molecular sieve.

[0022] In some of these embodiments, the mass ratio of the hard carbon material to the soft carbon material is (5-20):1.

[0023] In some of these embodiments, the first solvent is an organic solvent.

[0024] In some of these embodiments, the first solvent includes at least one of n-hexane, xylene, carbon disulfide, or carbon tetrachloride.

[0025] In some of these embodiments, the drying temperature is 80°C to 100°C.

[0026] In some of these embodiments, the calcination temperature is 1000℃~1300℃ and the time is 5h~10h.

[0027] In some embodiments, the molecular sieve raw material includes an aluminum source, additives, and a template agent.

[0028] In some of these embodiments, the mass ratio of the hard carbon material with a soft carbon coating, the aluminum source, the additives and the template agent is (2-5):(1-3):(1-2):(1-3).

[0029] In some of these embodiments, the hydrothermal reaction is carried out at a temperature of 150°C to 200°C for a duration of 1 hour to 2 hours.

[0030] In some embodiments, the heat treatment is performed at a temperature of 500°C to 600°C for 2 to 3 hours.

[0031] In some embodiments, the hard carbon material includes hard carbon micro powder, and the preparation method of the hard carbon micro powder includes: subjecting a hard carbon precursor to a first heat treatment, and when the first heat treatment temperature is reached, introducing a gas-phase pore-forming agent to activate and form pores, thereby obtaining an activated hard carbon precursor.

[0032] The activated hard carbon precursor was subjected to a second heat treatment under an inert atmosphere to obtain hard carbon micro powder.

[0033] In some of these embodiments, the hard carbon precursor is obtained by pre-carbonizing carbon raw materials.

[0034] In some embodiments, the carbon raw material includes at least one of phenolic resins, biomass, or bitumen.

[0035] In some embodiments, the pretreatment includes low-temperature carbonization at a temperature of 300°C to 500°C.

[0036] In some of these embodiments, the vapor-phase pore-forming agent includes at least one of carbon dioxide, oxygen, air, or water vapor.

[0037] In some of these embodiments, the temperature of the first heat treatment is 800°C to 900°C, and the time is 2 hours to 4 hours.

[0038] In some embodiments, the temperature of the second heat treatment is 1100°C to 1500°C, and the time is 5 hours to 10 hours.

[0039] According to another aspect of this application, an embodiment of this application provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode material, the negative electrode material being the aforementioned negative electrode material or a negative electrode material prepared according to the aforementioned preparation method.

[0040] According to another aspect of this application, an embodiment of this application provides a battery including a negative electrode sheet, wherein the negative electrode sheet is the aforementioned negative electrode sheet.

[0041] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0042] In this embodiment, after the hard carbon material is coated with a first coating layer (soft carbon), its specific surface area can be effectively reduced, improving its initial efficiency and also benefiting slurry processing in practical applications. Furthermore, after the hard carbon material is coated with the first coating layer, it also has a second coating layer. This second coating layer serves as a protective layer, preventing direct contact between the electrolyte and the active material, reducing side reactions, and improving the cycle stability of the negative electrode material. Moreover, the molecular sieve in the second coating layer has an ordered pore structure, allowing sodium ions to quickly reach the active layer. Without affecting sodium ion transport, it accelerates the sodium ion desolvation process, further improving the kinetic performance of the negative electrode material.

[0043] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0044] Figure 1 The diagram shown is a schematic diagram of a negative electrode material structure provided in Embodiment 1 of the present invention.

[0045] 1-Hard carbon material; 2-First coating layer; 3-Second coating layer. Detailed Implementation

[0046] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0047] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0048] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0049] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0050] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0051] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0052] To address the issues of numerous surface defects and large specific surface area in hard carbon as an anode material, leading to significant initial irreversible capacity loss, rapid cycle decay, and numerous surface side reactions, related technologies employ a non-metallic coating to prevent the electrolyte from contacting the hard carbon surface. However, this method also hinders sodium ions from entering the active material, resulting in poor rate performance and sodium deposition.

[0053] [Anode Material]

[0054] In view of this, the present application provides a negative electrode material, which includes: a hard carbon material 1, a first coating layer 2 covering at least a portion of the surface of the hard carbon material, and a second coating layer 3 covering at least a portion of the surface of the first coating layer 2;

[0055] The first coating layer 2 includes soft carbon;

[0056] The second coating layer 3 includes a molecular sieve.

[0057] In this application, after the hard carbon material 1 is coated with the first coating layer 2 (soft carbon), the specific surface area of ​​the hard carbon material 1 can be effectively reduced, the initial efficiency of the hard carbon material 1 can be improved, and it is also beneficial to the slurry processing in practical applications. Furthermore, after the hard carbon material 1 is coated with the first coating layer 2, it also has a second coating layer 3, which can serve as a protective layer to prevent the electrolyte from directly contacting the active material, reduce the occurrence of side reactions, and improve the cycle stability of the negative electrode material. Moreover, the molecular sieve in the second coating layer 3 itself has an ordered pore structure, which allows sodium ions to quickly reach the active layer. Without affecting the transport of sodium ions, it can accelerate the desolvation process of sodium ions, further improving the kinetic performance of the negative electrode material.

[0058] The term "molecular sieve" refers to a synthetically produced hydrated aluminosilicate (zeolite) or natural zeolite that has the ability to filter molecules. Its general chemical formula is (M′2M)O·Al₂O₃·xSiO₂·yH₂O, where M′ and M are monovalent and divalent cations, respectively, such as K₂O and K₂O. + Na + and Ca 2+ Ba 2+ Molecular sieves, etc., have numerous uniformly sized channels and neatly arranged pores. Different pore sizes allow molecular sieves to separate molecules of different sizes and shapes. Different pore sizes are obtained based on the different molecular ratios of SiO2 and Al2O3. Types include: 3A (potassium A type), 4A (sodium A type), 5A (calcium A type), 10Z (calcium Z type), 13Z (sodium Z type), Y (sodium Y type), sodium mordenite zeolite, etc.

[0059] In some specific embodiments, the thickness of the first coating layer 2 is 100 nm to 200 nm. As an example, the thickness of the first coating layer 2 can be any value among 100 nm, 130 nm, 170 nm, and 200 nm, or a range between any two. With the thickness of the first coating layer 2 within this range, the first efficiency of the hard carbon matrix can be effectively improved, and its high-temperature performance can be enhanced without affecting its excellent ion transport capability.

[0060] In some specific embodiments, soft carbon includes, but is not limited to, at least one of pitch-based soft carbon, tar-based soft carbon, or wood-based soft carbon. As an example, soft carbon can be pitch-based soft carbon or tar-based soft carbon.

[0061] In some specific embodiments, the thickness of the second coating layer 3 is 10 nm to 50 nm. For example, the thickness of the second coating layer 3 can be any value from 10 nm, 20 nm, 40 nm, and 50 nm, or a range between any two. Within this range, the thickness of the second coating layer 3 does not affect the rapid transport of active ions and serves as a protective layer.

[0062] In some specific embodiments, the second coating layer 3 includes a molecular sieve, which includes, but is not limited to, at least one of AlPO4-5, SiO2, or Al2O3. As an example, the molecular sieve can be AlPO4-5 or SiO2. In this invention, the molecular sieve is preferably AlPO4-5, as AlPO4-5 itself has excellent conductivity, which can further improve the conductivity of the hard carbon material 1, thereby reducing the overall internal resistance of the negative electrode material, avoiding overall capacity loss of the negative electrode material, and improving the overall cycle performance of the negative electrode material.

[0063] In some specific embodiments, the pore size of the molecular sieve is ≤2nm. As an example, the pore size of the molecular sieve can be 2nm, 1.8nm, 1.5nm, etc., or other values ​​within the above range, which are not limited here. A pore size within the above range facilitates the rapid passage of active ions.

[0064] In some specific embodiments, the particle size of hard carbon material 1 is 4µm to 10µm. As an example, the particle size of hard carbon material 1 can be 4µm, 6µm, 8µm, 10µm, etc., or other values ​​within the above range, which are not limited here. Hard carbon material 1 with a particle size within the above range can possess better performance.

[0065] In some specific embodiments, the hard carbon material 1 has a porous structure. The porous structure of the hard carbon material 1 can effectively shorten the ion transport distance in the negative electrode and improve the ion migration rate, thereby improving the rate performance of the negative electrode; at the same time, the porous structure also provides a large number of active sites for ions, significantly improving the battery capacity.

[0066] In some specific embodiments, the pore size of hard carbon material 1 is 2 nm to 10 nm. As an example, the pore size of hard carbon material 1 can be 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, etc., or other values ​​within the above range, which are not limited here. A pore size within the above range can provide better performance for hard carbon material 1.

[0067] In some specific embodiments, the porosity of hard carbon material 1 is 0.2% to 0.6%. As an example, the porosity of hard carbon can be 0.2%, 0.4%, 0.6%, etc., or other values ​​within the above range, which are not limited here. A porosity within the above range for hard carbon material 1 can satisfy better rate performance while ensuring higher capacity.

[0068] Therefore, based on the above scheme, after the hard carbon material 1 is coated with the first coating layer 2 (soft carbon), its specific surface area can be effectively reduced, improving its initial efficiency, and it is also beneficial for slurry processing in practical applications. Furthermore, after being coated with the first coating layer 2, the hard carbon material 1 also has a second coating layer 3. The second coating layer 3 serves as a protective layer, preventing direct contact between the electrolyte and the active material, reducing side reactions, and improving the cycle stability of the negative electrode material. Moreover, the molecular sieve in the second coating layer 3 has an ordered pore structure, allowing sodium ions to quickly reach the active layer. Without affecting sodium ion transport, it accelerates the sodium ion desolvation process, further improving the kinetic performance of the negative electrode material. Furthermore, the porous structure of the hard carbon material 1 can effectively shorten the ion transport distance on the negative electrode, increasing the ion migration rate and thus improving the rate performance of the negative electrode. Simultaneously, the porous structure also provides a large number of active sites for ions, significantly increasing battery capacity.

[0069] [Preparation methods for negative electrode materials]

[0070] Based on the same inventive concept, this application provides a method for preparing a negative electrode material, including the following steps:

[0071] Hard carbon material 1 and soft carbon material are mixed in a first solvent, dried, and then calcined to obtain hard carbon material 1 with a soft carbon coating layer on the surface.

[0072] Hard carbon material 1 with a soft carbon coating on its surface and molecular sieve raw material are mixed in a second solvent and subjected to a hydrothermal reaction. After heat treatment, the negative electrode material is obtained.

[0073] The negative electrode material includes: hard carbon material 1, a first coating layer 2 covering at least a portion of the surface of the hard carbon material 1, and a second coating layer 3 covering at least a portion of the surface of the first coating layer 2; the first coating layer 2 includes soft carbon; and the second coating layer 3 includes a molecular sieve.

[0074] It should be understood that all the characteristics and advantages described above regarding the "anode material" also apply to the "preparation method of the anode material," and will not be repeated here.

[0075] In some specific embodiments, the mass ratio of hard carbon material 1 to soft carbon material is (5-20):1. As an example, the mass ratio of hard carbon material 1 to soft carbon material can be 5:1, 10:1, 15:1, 20:1, etc., or other values ​​within the above range, which are not limited here.

[0076] In some specific embodiments, the first solvent is an organic solvent.

[0077] In some specific embodiments, the first solvent includes, but is not limited to, at least one of n-hexane, xylene, carbon disulfide, or carbon tetrachloride. As an example, the first solvent may be n-hexane, xylene, or a mixture of both.

[0078] In some specific embodiments, the drying temperature is 80℃ to 100℃. As an example, the drying temperature can be 80℃, 90℃, 100℃, etc., or other values ​​within the above range, which are not limited here.

[0079] In some specific embodiments, the calcination temperature is 1000℃~1300℃, and the time is 5h~10h. As examples, the calcination temperature can be 1000℃, 1100℃, 1200℃, 1300℃, etc., or other values ​​within the above range, which are not limited here. The calcination time can be 5h, 6h, 8h, 10h, etc., or other values ​​within the above range, which are not limited here. After calcination, a first coated carbon layer is formed. Furthermore, if the calcination temperature is below 1000℃, the first coated carbon layer will have more defects, affecting the initial efficiency improvement; if the calcination temperature is above 1300℃, the first coated carbon layer will further hinder ion transport.

[0080] In some specific implementations, the molecular sieve raw materials include an aluminum source, additives, and template agents.

[0081] In some specific embodiments, the mass ratio of the hard carbon material 1 with a soft carbon coating layer, the aluminum source, the additives, and the template agent is (2-5):(1-3):(1-2):(1-3). As an example, the mass ratio of the hard carbon material 1 with a soft carbon coating layer, the aluminum source, the additives, and the template agent can be 2:1:1:1, 3:2:1.5:2, 5:3:2:3, etc., or other values ​​within the above range, which are not limited here. Maintaining the mass ratio of each raw material within the above range can effectively control the thickness of the second coating layer.

[0082] In some specific embodiments, the hydrothermal reaction temperature is 150℃~200℃, and the time is 1h~2h. As examples, the hydrothermal reaction temperature can be 150℃, 170℃, 200℃, etc., or other values ​​within the above range, which are not limited here. The time can be 1h, 1.5h, 2h, etc., or other values ​​within the above range, which are not limited here.

[0083] In some specific embodiments, the heat treatment temperature is 500℃~600℃, and the time is 2h~3h. As examples, the heat treatment temperature can be 500℃, 550℃, 600℃, etc., or other values ​​within the above range, which are not limited here. The time can be 2h, 2.5h, 3h, etc., or other values ​​within the above range, which are not limited here. After high-temperature heat treatment, the molecular sieve structure is more complete and can better coat the surface of the hard carbon anode.

[0084] [Preparation of Hard Carbon Material 1]

[0085] In some specific embodiments, the hard carbon material 1 includes hard carbon micro powder, and the preparation method of hard carbon micro powder includes: subjecting the hard carbon precursor to a first heat treatment, and when the first heat treatment temperature is reached, introducing a gas phase pore-forming agent to activate and form pores, thereby obtaining an activated hard carbon precursor.

[0086] The activated hard carbon precursor was subjected to a second heat treatment under an inert atmosphere to obtain hard carbon micro powder.

[0087] After the above treatment, the hard carbon precursor can be used to obtain hard carbon material 1 with a porous structure. The porous structure in hard carbon material 1 can effectively shorten the ion transport distance in the negative electrode and improve the ion migration rate, thereby improving the rate performance of the negative electrode. At the same time, the porous structure also provides a large number of active sites for ions, significantly improving the battery capacity.

[0088] In some specific embodiments, the hard carbon precursor is obtained by pre-carbonizing carbon raw materials.

[0089] In some specific embodiments, the carbon raw material includes, but is not limited to, at least one of phenolic resins, biomass, or bitumen. As an example, the carbon raw material can be a phenolic resin or bitumen; for instance, phenolic resin can be selected as the carbon raw material.

[0090] In some specific embodiments, the pretreatment includes low-temperature carbonization at a temperature of 300°C to 500°C. As an example, the temperature for low-temperature carbonization can be 300°C, 400°C, 500°C, etc., or other values ​​within the above range, and is not limited here. Low-temperature carbonization removes volatiles and forms carbon materials.

[0091] In some embodiments, the vapor-phase pore-forming agent includes, but is not limited to, at least one of carbon dioxide, oxygen, air, or water vapor. As an example, the vapor-phase pore-forming agent may be carbon dioxide, oxygen, or air.

[0092] In some specific embodiments, the temperature of the first heat treatment is 800℃~900℃, and the time is 2h~4h. As an example, the temperature of the first heat treatment can be 800℃, 850℃, 900℃, etc., or other values ​​within the above range, which are not limited here. The time can be 2h, 3h, 4h, etc., or other values ​​within the above range, which are not limited here.

[0093] In some specific embodiments, the temperature of the second heat treatment is 1100℃ to 1500℃, and the time is 5h to 10h. As an example, the temperature of the second heat treatment can be 1100℃, 1200℃, 1300℃, 1400℃, 1500℃, etc., or other values ​​within the above range, which are not limited here. The time can be 5h, 8h, 10h, etc., or other values ​​within the above range, which are not limited here.

[0094] In some specific embodiments, after the second heat treatment, the process further includes pickling, washing with water, drying, and sieving. For example, hydrochloric acid with a molar concentration of 1 mol / L can be used for washing.

[0095] Furthermore, the washing step specifically includes washing the product with water until it is neutral.

[0096] Furthermore, the material is sieved through a 300-350 mesh sieve. For example, it could be sieved through a 300 mesh sieve or a 325 mesh sieve.

[0097] After the first and second heat treatments described above, a hard carbon material 1 with excellent structure was prepared.

[0098] Therefore, based on the above scheme, after the hard carbon material 1 is coated with the first coating layer 2 (soft carbon), its specific surface area can be effectively reduced, improving its initial efficiency, and it is also beneficial for slurry processing in practical applications. Furthermore, after being coated with the first coating layer 2, the hard carbon material 1 also has a second coating layer 3. The second coating layer 3 serves as a protective layer, preventing direct contact between the electrolyte and the active material, reducing side reactions, and improving the cycle stability of the negative electrode material. Moreover, the molecular sieve in the second coating layer 3 has an ordered pore structure, allowing sodium ions to quickly reach the active layer. Without affecting sodium ion transport, it accelerates the sodium ion desolvation process, further improving the kinetic performance of the negative electrode material. Furthermore, the porous structure of the hard carbon material 1 can effectively shorten the ion transport distance on the negative electrode, increasing the ion migration rate and thus improving the rate performance of the negative electrode. Simultaneously, the porous structure also provides a large number of active sites for ions, significantly increasing battery capacity.

[0099] Based on the same inventive concept, this application provides a battery including a negative electrode sheet, the negative electrode sheet including a negative electrode material, the negative electrode material being the aforementioned negative electrode material or a negative electrode material prepared according to the aforementioned preparation method.

[0100] [Preparation of negative electrode sheet]

[0101] The negative electrode material, binder, and conductive agent are mixed in a solvent, coated onto the current collector, and dried to obtain the negative electrode sheet.

[0102] In some specific embodiments, the mass ratio of the negative electrode material, binder, and conductive agent is (93-97):(3-5):(0.5-1.5). As an example, the mass ratio of the negative electrode material, binder, and conductive agent can be any one of 93:3:0.5, 95:4:1, or 97:5:1.5, or any range between two of them.

[0103] In some specific embodiments, the current collector includes at least one of copper foil, nickel foam, nickel mesh, or composite copper foil. As an example, the current collector can be copper foil, nickel foam, etc.

[0104] In some specific embodiments, the coating thickness of the slurry is 300 μm.

[0105] In some specific embodiments, drying is carried out in a vacuum drying oven at a temperature of 70–90°C for a time of 10–15 hours. As an example, the drying temperature can be any value from 70°C, 80°C, and 90°C, or a range between any two. The drying time can be any value from 10 hours, 12 hours, 14 hours, and 15 hours, or a range between any two.

[0106] In some specific implementations, after the negative electrode sheet is prepared, it can be cut into the required size by a cutting tool.

[0107] Because the battery contains a negative electrode sheet made of the negative electrode material provided in the embodiments of this application, it has the advantage of improving its initial efficiency and cycle stability without affecting other battery performance.

[0108] In some specific embodiments, the battery can be a sodium-ion battery. The battery stacking type is, for example, a wound or stacked battery, and the structural type is, for example, a prismatic (aluminum, steel, etc.) battery, a pouch battery, or a cylindrical battery, etc., without specific limitations. This battery has excellent initial efficiency and cycle stability.

[0109] In some specific embodiments, the battery further includes a positive electrode, an electrolyte, and a separator. That is, the battery includes a positive electrode, a negative electrode, an electrolyte, and a separator.

[0110] In some specific embodiments, the positive electrode material and structure are not limited, and positive electrode structures and compositions known in the art that can be used in secondary batteries can be selected.

[0111] In some specific embodiments, the type of separator is not limited, and any separator known in the art that can be used in secondary batteries can be selected.

[0112] It should also be noted that the battery in this application does not limit the specific material or type of electrolyte. Any components and types known in the art that can be used in secondary batteries can be selected, as long as the purpose of this application can be achieved.

[0113] Since the battery provided in this embodiment of the invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be repeated here.

[0114] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0115] Example 1

[0116] Take 100g of coconut shell-based hard carbon precursor, put it into a carbonization furnace, heat it to 900℃ at a heating rate of 5℃ / min, introduce CO2 gas, and keep it at this temperature for 3h for activation treatment. Take out the treated product and put it into a high-temperature carbonization furnace for high-temperature carbonization. Heat it to 1300℃ under an argon atmosphere, keep it at this temperature for 8h, take it out, wash it with hydrochloric acid, wash it with water until neutral, dry it, and sieve it with a 325-mesh sieve to obtain hard carbon material.

[0117] Take 50g of the above-mentioned hard carbon material and add it to n-hexane solvent containing asphalt (soft carbon). The mass ratio of hard carbon to asphalt is 5:1. Heat and stir at 100°C until the solvent is completely evaporated. Then place it in a carbonization furnace with argon atmosphere and heat to 1000°C. Hold for 5 hours to obtain hard carbon material with soft carbon coating on the surface.

[0118] The hard carbon material with a soft carbon coating was uniformly dispersed in deionized water. ALOOH, phosphoric acid, and triamine were added sequentially in a mass ratio of 2:2:1:2. After stirring until dissolved, the mixture was poured into a reaction vessel and hydrothermally treated at 115°C for 1 hour. Finally, the collected powder was subjected to high-temperature heat treatment at 500°C for 2 hours to obtain the material. The structure of the negative electrode material is shown in the appendix of the instruction manual. Figure 1 .

[0119] Example 2

[0120] The difference between Example 2 and Example 1 is that the mass ratio of the hard carbon material with soft carbon coating to ALOOH, phosphoric acid and triamine in Example 2 is 5:2:1:2.

[0121] Example 3

[0122] The difference between Example 3 and Example 1 is that Example 3 uses phenolic resin as a hard carbon precursor.

[0123] Example 4

[0124] The difference between Example 4 and Example 1 is that Example 4 uses tar instead of asphalt in Example 1.

[0125] Example 5

[0126] The difference between Example 5 and Example 1 is that the steps for preparing hard carbon material in Example 5 include: taking 100g of coconut shell-based hard carbon precursor, placing it in a carbonization furnace, heating it to 800℃ at a heating rate of 6℃ / min, introducing CO2 gas, and holding it at this temperature for 4h for activation treatment, taking out the treated product and placing it in a high-temperature carbonization furnace for high-temperature carbonization, heating it to 1400℃ under an argon atmosphere, holding it at this temperature for 7h, taking it out, washing it with hydrochloric acid and then washing it with water until neutral, drying it, and sieving it using a 325-mesh sieve to obtain hard carbon material.

[0127] Example 6

[0128] The difference between Example 6 and Example 1 is that in Example 6, the hard carbon material with soft carbon coating, sodium silicate, NaOH and tetrapropylammonium hydroxide were stirred and dissolved evenly in a mass ratio of 2:2:1:2, and then poured into a reaction vessel. The mixture was hydrothermally treated at 15°C for 1 hour, and finally the collected powder was subjected to high-temperature heat treatment at 500°C for 2 hours to prepare the material.

[0129] Comparative Example 1

[0130] The difference between Comparative Example 1 and Example 1 is that the hard carbon material with soft carbon coating on the surface of Comparative Example 1 is mixed only with ALOOH and phosphoric acid in a mass ratio of 2:2:1.

[0131] Comparative Example 2

[0132] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 only applies soft carbon coating to hard carbon materials.

[0133] Comparative Example 3

[0134] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 only coats the hard carbon material with a porous AlPO4-5 coating.

[0135] Performance testing

[0136] 1. Battery manufacturing

[0137] The negative electrode materials prepared in each embodiment and comparative example were uniformly mixed with conductive carbon black (SP):carboxymethyl cellulose (CMC):styrene-butadiene rubber (SBR) in a ratio of 95:1:1.5:2.5 (mass ratio) and coated onto copper foil. The coated electrode sheets were then dried in a vacuum drying oven at 80°C for 12 hours. Simulated battery assembly was performed in an argon-protected Braun glove box. The electrolyte was 1 mol NaPF6-EC / DEC (volume ratio 1:1) + 5% fluoroethylene carbonate (FEC), the separator was glass fiber, and the counter electrode was a sodium metal sheet. CR2032 button cells were assembled in the glove box.

[0138] 2. Electrochemical performance testing

[0139] First Coulombic Efficiency Test: The sodium-ion half-cells assembled in each example and comparative example were subjected to the first efficiency test. The specific procedure is as follows: 1) (25±2)℃ for 2 hours; 2) Charged to 0V with a constant current of 0.05C, allowed to stand for 5 minutes, and then charged to 0V with a constant current of 20uA to obtain the first charge capacity; 3) Allowed to stand for 5 minutes; 4) Discharged to 2.0V with a constant current of 0.05C to obtain the first discharge capacity; 5) Allowed to stand for 5 minutes (First Coulombic Efficiency (ICE) = First Discharge Capacity / First Charge Capacity).

[0140] Rate performance test: At (25±2)℃, discharge at 0.1C constant current to 2V, let stand for 5min, charge at 2C constant current and constant voltage to 0V, cut-off current is 0.05C, record the ratio of the capacity of constant current and constant voltage charging to the capacity of constant current charging, which is the charging constant current ratio.

[0141] 200-cycle retention rate test: At (25±2)℃, charge to 0V with constant current and constant voltage at 0.05C, cut off current at 0.02C, let stand for 5min, then discharge to 2V with constant current at 0.05C, let stand for 5min, and record the ratio of the discharge capacity of the 200th cycle to the initial discharge capacity, which is the capacity retention rate.

[0142] The specific test results for the above items are shown in Table 1.

[0143] Table 1

[0144]

[0145] As can be seen from the table, the initial coulombic efficiency of Comparative Example 3 is relatively low, indicating that the soft carbon coating can effectively improve the initial efficiency. Compared with Examples 1 and 2, Comparative Example 1 shows poorer rate performance, proving that triethylamine serves as a template for the porous coating, and the porous structure is beneficial to the transport of sodium ions. Meanwhile, compared with Comparative Example 2, Example 1 exhibits higher rate performance, indicating that the porous structure can also accelerate the transport of sodium ions. + The desolvation process further enhances the kinetics. From the cycling results, Example 1 exhibits the best cycle retention rate, indicating that the formation of the AlPO4-5 coating effectively improves the cycle retention rate and prevents direct contact with the electrolyte, thus avoiding excessive consumption of active sodium. In Example 2, the cycle retention rate slightly decreases with increasing hard carbon content. Furthermore, comparing Example 1 and Comparative Example 3, it is evident that soft carbon coating also contributes to improving cycle stability to some extent, which may be mainly attributed to the improved first-efficiency.

[0146] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0147] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.

[0148] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0149] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0150] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode material, characterized in that, The negative electrode material includes: hard carbon material, a first coating layer covering at least a portion of the surface of the hard carbon material, and a second coating layer covering at least a portion of the surface of the first coating layer; The first coating layer comprises soft carbon; The second coating layer includes a molecular sieve; The second coating layer includes a molecular sieve, wherein the molecular sieve includes AlPO4-5; The method for preparing the negative electrode material includes the following steps: Hard carbon material and soft carbon material are mixed in a first solvent, dried, and then calcined to obtain a hard carbon material with a soft carbon coating layer on the surface. Hard carbon material with a soft carbon coating on its surface and molecular sieve raw material are mixed in a second solvent and subjected to a hydrothermal reaction. After heat treatment, the negative electrode material is obtained. The mass ratio of the hard carbon material to the soft carbon material is (5~20):1; The first solvent is an organic solvent; The first solvent includes at least one of n-hexane, xylene, carbon disulfide, or carbon tetrachloride; The drying temperature is 80℃~100℃; The calcination temperature is 1000℃~1300℃, and the time is 5h~10h; The molecular sieve raw materials include an aluminum source, additives, and a template agent; The mass ratio of the hard carbon material with a soft carbon coating layer on the surface, the aluminum source, the additives and the template agent is (2~5):(1~3):(1~2):(1~3); The hydrothermal reaction is carried out at a temperature of 150℃~200℃ for 1h~2h. The heat treatment temperature is 500℃~600℃, and the time is 2h~3h; The aluminum source is selected from ALOOH, the auxiliary agent is selected from phosphoric acid, and the template agent is selected from triamine.

2. The negative electrode material according to claim 1, characterized in that, The thickness of the first coating layer is 100nm~200nm; And / or, the soft carbon includes at least one of pitch-based soft carbon, tar-based soft carbon, or wood-based soft carbon.

3. The negative electrode material according to claim 1, characterized in that, The thickness of the second coating layer is 10nm~50nm; And / or, the pore size of the molecular sieve is ≤2nm.

4. The negative electrode material according to claim 1, characterized in that, The particle size of the hard carbon material is 4µm to 10µm. And / or, the hard carbon material has a porous structure; The hard carbon material has a pore size of 2 nm to 10 nm. The porosity of the hard carbon material is 0.2% to 0.6%.

5. The negative electrode material according to claim 1, characterized in that, The hard carbon material includes hard carbon micro powder, and the preparation method of the hard carbon micro powder includes: subjecting the hard carbon precursor to a first heat treatment, and when the first heat treatment temperature is reached, introducing a gas phase pore-forming agent to activate and form pores, thereby obtaining an activated hard carbon precursor. The activated hard carbon precursor was subjected to a second heat treatment under an inert atmosphere to obtain hard carbon micro powder.

6. The negative electrode material according to claim 5, characterized in that, The preparation method of the hard carbon micro powder satisfies at least one of the following features (1) to (4): (1) The hard carbon precursor is obtained by pre-carbonization treatment of carbon raw materials; The carbon raw material includes at least one of phenolic resin, biomass, or bitumen; The pre-carbonization treatment includes a low-temperature carbonization treatment at a temperature of 300℃~500℃; (2) The gas phase pore-forming agent includes at least one of carbon dioxide, oxygen, air or water vapor; (3) The temperature of the first heat treatment is 800℃~900℃ and the time is 2h~4h; (4) The temperature of the second heat treatment is 1100℃~1500℃ and the time is 5h~10h.

7. A negative electrode sheet, said negative electrode sheet comprising a negative electrode material, characterized in that, The negative electrode material is the negative electrode material according to any one of claims 1 to 6.

8. A battery comprising a negative electrode, characterized in that, The negative electrode is the negative electrode as described in claim 7.

Citation Information

Patent Citations

  • Sodium ion battery negative electrode material and preparation method thereof

    CN109742399A

  • Modified amorphous material and preparation method thereof, negative plate and sodium ion battery

    CN115991473A